Ascorbyl Palmitate Hydrogel for Local, Intestinal Delivery of Macromolecules - Jinyi Zhai; Julia Mantaj; Driton Vllasaliu (MDPI AG, 2018)
Biologics have changed the management of inflammatory bowel disease (IBD), but there are concerns with unexpected systemic toxicity and loss of therapeutic response following administration by injection. Rectal administration of biologics offers potentially reduced therapy costs, as well as safer and more effective local delivery to inflammation sites. Hydrogels are potentially useful carriers of biologics for improved delivery to the inflamed intestinal mucosa. Here, we prepared a hydrogel system based on ascorbyl palmitate (AP) and incorporated a model macromolecular drug (fluorescently-labelled dextran) into the system. Characterization of gel properties included rheology, drug loading and release, cytotoxicity, and drug delivery in an in vitro intestinal model. We report that this hydrogel can be formed under a moderate environment that is amenable to incorporation of some biologics. The system showed a shear-thinning behavior. AP hydrogel released approximately 60% of the drug within 5 h and showed reasonable a cytotoxicity profile. The study therefore provides evidence that AP hydrogel has potential for local delivery of macromolecules to the intestinal mucosa in IBD.